Mimics of small ribozymes utilizing a supramolecular scaffold - Lonnberg TA; Helkearo M; Jancso A; Gajda T (ROYAL SOC CHEMISTRY, 2022)
For elucidating the mechanism of the general acid/base catalysis of the hydrolysis of RNA phosphodiester bonds, a number of cleaving agents having two cyclen moieties tethered to a 1,3,5-triazine core have been prepared and their ability to bind and cleave uridylyl-3', 5'-uridine (UpU) studied over a wide pH range. Around neutral pH, the cleaving agents form a highly stable ternary complex with UpU and Zn-II through coordination of the uracil N3 and the cyclen nitrogen atoms to the Zn-II ions. Under conditions where the triazine core exists in the deprotonated neutral form, hydrolysis of UpU, but not of adenylyl-3',5'-adenosine (ApA), is accelerated by approximately two orders of magnitude in the presence of the cleaving agents, suggesting general base rather than metal ion catalysis. The probable mechanism of the observed catalysis and implications to understanding the general acid/base-catalyzed phosphodiester hydrolysis by ribozymes are discussed.